2013
DOI: 10.1111/hir.12022
|View full text |Cite
|
Sign up to set email alerts
|

The role of readability in effective health communication: an experiment using a Japanese health information text on chronic suppurative otitis media

Abstract: Objectives: This study identifies the most significant readability factors and examines ways of improving and evaluating Japanese health information text in terms of ease of reading and understanding. Methods: Six different Japanese texts were prepared based on an original short text written by a medical doctor for a hospital web site intended for laypersons regarding chronic suppurative otitis media. Four were revised for single readability factor (syntax, vocabulary, or text structure) and two were modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Multiple studies across a variety of health topics have further indicated that users prefer messages that are positive in tone or benefit-oriented, brief, and direct [17,18]. Moving beyond user preferences, some recent research has specifically focused on the impact of the underlying characteristics of text on readability and retention [19,20]. For example, Leroy and colleagues [20] revealed that, although low noun-phrase complexity was perceived by users as the simplest, grammatical manipulations had little impact on the readability of the content.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies across a variety of health topics have further indicated that users prefer messages that are positive in tone or benefit-oriented, brief, and direct [17,18]. Moving beyond user preferences, some recent research has specifically focused on the impact of the underlying characteristics of text on readability and retention [19,20]. For example, Leroy and colleagues [20] revealed that, although low noun-phrase complexity was perceived by users as the simplest, grammatical manipulations had little impact on the readability of the content.…”
Section: Introductionmentioning
confidence: 99%
“…These online articles exceed the American average reading comprehension level of seventh grade, which implies that the comprehension of information is likely beyond their reading capacity and viewers might not have found the information useful (Walsh & Volsko, 2008). Similarly, Sakai’s experiment suggested that improving the vocabulary choices within health information could significantly improve the reader’s comprehension of information (Sakai, 2013).…”
mentioning
confidence: 99%
“…Firstly, by conducting aspectual analysis to understand the significance of seminal papers, which is a step beyond the point of merely collecting and categorising data. Sakai concluded that vocabulary has the highest critical factor in preparing quality patient information (Sakai, ). Clarke et al.…”
Section: Discussion: Making Sense Of the Diversity Of Seminal Papersmentioning
confidence: 99%